2007
DOI: 10.1149/1.2781033
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Mechanism of Platinum in Acidic Media

Abstract: The platinum solubility in a polymer electrolyte would be a key issue in order to improve and guarantee the durability of PEFCs. In this study, the platinum solubility has been determined in acidic electrolytes as a function of temperature and pH. The solubility was ca. 3 x 10-6 mol dm-3 at 25oC in 1 mol dm-3 of H2SO4, HClO4, and CF3SO3H under air, and increased with temperature and with the decrease in pH. The platinum solubility in oxygen was slightly larger than that in air. However, the solubility in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Microprobe analysis of the NiPS 3 and FePS 3 electrode tips after CA experiments using the platinum CE shows M/P/S elements, but Pt, if present, is below detection limits (Supplementary Figure S10). The results of the platinum CE track well with other reports describing the possibility of platinum ion migration from platinum counter electrodes that can impact metal catalyst stability in fuel cells and apparent catalyst activity in HER, particularly under acidic conditions and in the presence of oxygen-rich environments [60][61][62][63]. Graphite working electrodes show a significant increase in HER activity over time when using a platinum CE [64].…”
Section: Examination Of Electrocatalytic Her Activity For Mps 3 Productssupporting
confidence: 87%
“…Microprobe analysis of the NiPS 3 and FePS 3 electrode tips after CA experiments using the platinum CE shows M/P/S elements, but Pt, if present, is below detection limits (Supplementary Figure S10). The results of the platinum CE track well with other reports describing the possibility of platinum ion migration from platinum counter electrodes that can impact metal catalyst stability in fuel cells and apparent catalyst activity in HER, particularly under acidic conditions and in the presence of oxygen-rich environments [60][61][62][63]. Graphite working electrodes show a significant increase in HER activity over time when using a platinum CE [64].…”
Section: Examination Of Electrocatalytic Her Activity For Mps 3 Productssupporting
confidence: 87%
“…In the latter case, Pd oxidation is caused by the place-exchange process between O and Pt in MLs. In the regime over 1 V, the preferential Pd oxidation presumably prevents the oxidation of Pt MLs, and thus, it imparts a certain degree of cathodic protection for Pt MLs. , At 1.51 V, the percentage of the oxide formation in Pt MLs is 21%, which is 3.6 times smaller than that of Pt/C (76% in Figure b; see also Figure S9). On the other hand, at the same potential, the percentage of PdO in Pd cores is 15%, which corresponds to 34% of Pd atoms on the surface of Pd cores (assuming that Pd oxidation occurs exclusively through the place-exchange mechanism and the N s / N t is ca.…”
Section: Resultsmentioning
confidence: 97%
“…Membrane electrode assembly (MEA) tests of the Pt ML electrocatalysts also demonstrated exceptional long-term stability. , The atomic structure of the Pt ML /Pd/C electrocatalyst was examined using in situ EXAFS, and the formation of Pt MLs on Pd nanoparticle surfaces and the contraction in Pt–Pt distance were confirmed . The EXAFS analysis also demonstrated that the Pt ML structure was almost retained after 60 000 potential cycles in MEA tests . In situ XAS studies provide information only from the Pt ML atoms on the surface of the metal nanoparticles that participate in electrocatalytic reactions; thus, direct and unambiguous comparison between electronic/structural properties of a catalyst and its activity can be made.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations